PELABELAN TOTAL TAK-AJAIB SISI PADA MULTISTAR - Yoga Jati Kusuma; Dominikus Arif Budi Prasetyo (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2020)
Graph theory contains several topics, one of which will be discussed in this study is graph labeling. In the topic of labeling, the graph used is a limited, simple, and undirected graph. In this study, the type of labeling used is total labeling. The multistar graph used in this study is a combination of star graphs whose center vertex are not connected to each other. This research uses literature research method which is divided into two parts, that is the basic calculation to determine the boundary of the first term ???????? and the difference ???????? from the (????????,????????) edge antimagic total labeling on the ???????????????????????? multistar graph. The second part is to apply (????????,????????) edge antimagic total labeling to the multistar graph ????????????????????????. In multistar ???????????????????????? can be labeled by (????????,????????) edge antimagic total labeling by ????3????????2????????2+5????????2????????+4???????????? 2???????????? ,1???? and ????2????????2????????2+5????????2????????+5???????????? 2???????????? ,2???? for center label smallest value, with ????????≥1 and ????????≥2. Otherwise, for center label largest value can be done by ????7????????2????????2+????????2????????+4???????????? 2???????????? ,1????and ????6????????2????????2+????????2????????+5???????????? 2???????????? ,2???? with ????????≥1 and ????????≥2.